ZAKAT MANAGEMENT IN TURKI AND INDONESIA - Muhammad Ramadhan; Melani Azzahra Nur; Maryam Batubara (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
Zakat management is a crucial aspect in the Islamic economic system, which plays an important role in overcoming poverty and improving the welfare of Muslims. This journal examines zakat management in Turkey, a country with a majority Muslim population and a rich Islamic history. By focusing on the role of zakat institutions and cooperation between the government and zakat organizations, this research presents an overview of zakat management practices in Turkey. There are many Islamic countries that are successful in managing zakat, one of which is the United Arab Emirates. This research aims to find out how zakat is managed in Turkey and how it differs from zakat management in Indonesia. This research uses a qualitative approach with library research methods. The results of his research are that zakat funds in Turkey are managed by Zakat managed by several communities or charitable foundations such as the Turkish Red Crescent Kizilay, the Turkiye Diyanet Foundation and IHH Insani Yardim Vakfi.